IN TRANSITION BUT NEVER UNDONE?: CONTESTING MASCULINITY - Chadwick, Rachelle; Foster, Don (PINS-Psychology in Society, 2025)
This paper attempts to “trouble” the widespread assumption that South African masculinities are currently in flux. It argues that a rhetoric heralding the rise of alternative masculinities is nothing new and shows how the talk of white, privileged men, while ostensibly eschewing traditional masculinity, often ultimately works to re inscribe rather than undo the centrality of masculinity. The paper also argues for a more theoretically nuanced analysis of masculinity which resists the urge to reduce masculinity to the realm of individualist subjectivity and which recognises the overdetermined interpenetration of ideology, power relations and socio-material constraints in the reproduction of subjectivity.